2022
DOI: 10.1093/jjco/hyac070
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of radiculopathy caused by second course of spine stereotactic body radiotherapy

Abstract: Objective Stereotactic body radiotherapy is used to treat spinal metastases; however, 10% of patients experience local failure. We aimed to clarify the outcomes of the second course of stereotactic body radiotherapy for spinal metastases with a uniform fractionation schedule at our institution. Methods Data of patients treated with a second salvage stereotactic body radiotherapy course at the same spinal level or adjacent lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Herein, we discussed the optimal dose–fraction schedules for SBRT2 based on published studies. Two retrospective studies of SBRT2 in spinal metastases have reported [ 13 , 18 ] delivering 30 Gy in four fractions (median dose) [ 18 ] and 30 or 35 Gy in five fractions [ 13 ]. The latter revealed the absence of LF within 1 year or RM in 19 lesions [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, we discussed the optimal dose–fraction schedules for SBRT2 based on published studies. Two retrospective studies of SBRT2 in spinal metastases have reported [ 13 , 18 ] delivering 30 Gy in four fractions (median dose) [ 18 ] and 30 or 35 Gy in five fractions [ 13 ]. The latter revealed the absence of LF within 1 year or RM in 19 lesions [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prescribed SBRT2 dose was 30 Gy delivered in five fractions on the basis of a previous retrospective case series [ 13 , 18 ]. The objective was to guarantee that 95% of the PTV received the prescribed dose, while ensuring that the normal tissues adhered to dose constraints.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SBRT technique has been discussed in great detail in previous publications [15,16] and is briefly summarized here. The clinical target volume included the gross tumor and the immediately adjacent bony anatomic compartments at risk of microscopic disease extension, as described by the contouring guidelines for spine SBRT [17,18].…”
Section: Spine Sbrtmentioning
confidence: 99%